Critical vasospasm during fingolimod (fty720) treatment in a patient with multiple sclerosis - Schwarz, Alexander; Korporal-Kuhnke, Mirjam; Hosch, Waldemar P.; Max, R.; Wildemann, Brigitte (Neurology, 2010)
We report on a woman who developed critical arterial vasospasm of the left arm within 7 days after having started treatment with Fingolimod (FTY720). Fingolimod is an orally administered modulator of the sphingosine-1-phosphate (S1P) receptor family, acting at 4 of the 5 G protein-coupled S1P receptors. It causes a reversible sequestration of lymphocytes into lymph nodes, thereby inhibiting their migration to sites of inflammation. Fingolimod is currently tested in clinical trials for the treatment of relapsing-remitting multiple sclerosis (RRMS). As S1P receptors regulate numerous cellular processes in different tissues, Fingolimod exhibits the capacity to induce versatile pharmacologic effects.
Gesehen am 06.07.2023